KAP study on emergency contraception among women of reproductive age group attending JNUIMSRC OPD, Jaipur, India - Meena, Pragati; Meena, Seema; Choudhary, Richa; Sharma, Bharti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Unintended pregnancy, unplanned birth and unsafe abortion have been a major challenge to the reproductive health of women worldwide. Despite the availability of highly efficient contraceptive technologies, there are still many undesired pregnancies that put women at a higher risk of mortality, frequently as a result of unsafe abortion. Emergency contraceptive pills can be used to prevent these unwanted pregnancies. Aim of this study was to assess the knowledge, attitude and practice of use of emergency contraception among women of reproductive age group attending JNUIMSRC OPD, Jaipur, India. Methods: Institution based cross-sectional study was conducted among 100 females of reproductive age group attending JNUIMSRC OPD, Jaipur, India. Data was collected using pretested semi-structured questionnaire after written informed consent. Descriptive and inferential statistics were used to analyse the data generated. Results: Among respondents who were aware of ECPs, 64% had good knowledge of it, 90% had positive attitude towards ECPs and 63% have used earlier. A significant association was found between age, residence, educational level and occupational status with awareness of ECPs. Conclusions: Awareness and utilization of emergency contraceptive pills is low among females of reproductive age group attending OPD at JNUIMSRC. Thus awareness should be enhanced through formal education, communication from healthcare professionals and media that can offer trustworthy and accurate information on ECPs.